Accessing cryptic diversity in Neotropical rattlesnakes (Serpentes: Viperidae: Crotalus) with the description of two new species - Carbajal-Márquez, Rubén Alonso; Cedeño-Vázquez, José Rogelio; Martínez-Arce, Arely; Neri-Castro, Edgar; Machkour- M’rabet, Salima C. (Zootaxa, 2020)
Members of the Crotalus durissus species complex are widely distributed from Mexico to Argentina in areas with mainly seasonally dry tropical deciduous forest. Although four species (C. culminatus, C. durissus, C. simus and C. tzabcan) are currently recognized, species limits remain to be tested. Previous genetic studies suggest that C. durissus and C. simus may be paraphyletic and that at least one cryptic species may be present. We analyzed 2596 bp of DNA sequence data from three mitochondrial and one nuclear gene to infer phylogenetic relationships in the Neotropical rattlesnakes. We also examined museum and wild specimens as well as captive animals to analyze morphological characters. Our results suggest that the current taxonomy of the Crotalus durissus species complex does not reflect evolutionary history. We found strong support for five independent lineages within Crotalus simus (sensu lato), with genetic and morphological evidence for three previously recognized taxa and two new species, as well as three major lineages within C. durissus that each represent species hypothesis to be tested with additional evidence. We also found support to retain C. totonacus in the Crotalus molossus species complex. We suggest conservative taxonomic changes to the complex and related species, but more evidence is needed (e.g., morphology, ecology and venom composition) to clarify relationships among species.